Challenges Faced by Faculty of Medical Education Due to the Structural Variation in its Departments across Medical Colleges - Shaista Noor Qureshi, Rehan Ahmed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To explore the challenges faced by faculty of medical education due to structural variation of Department of Medical Education (DME). Study Design: Qualitative study Place and duration of study: Islamic International Medical College, Riphah International University Rawalpindi from 1st March to 31st August 2022. Methodology: Interviews were taken from 11 DME faculty members through Zoom which were recorded and transcribed. Coding of data and thematic analysis were conducted manually. Results: The current setups of DME showed variation in hierarchical structure, they are having minimum one member or maximum five members. The challenges faced by Health Professions Educationists due to structural variation are lack of trained, experienced and qualified faculty, support staff, infrastructure, funds, resistance from faculty and administration. Internal and external politics, lack of authority and no autonomy results in demoralizing the morale of DME. Conclusion: The number of faculty members, support staff and the hierarchy of DME is left completely to the discretion of the medical college management. Trained faculty, protected time for research, proper hierarchical structure and provision of funds may facilitate in achievement of basic and quality standards set by accreditation bodies. Key words: Department of medical education (DME), Health professions education, Medical educationist, Hierarchical structure